Securing cluster based routing against cooperative black hole attack in mobile ad hoc network - Selvam Raman, Pandi; K, Shankar; M, Ilayaraja (International Journal of Engineering and Technology, 2018)
Mobile ad hoc networks (MANETs) are wireless infrastructure-less network consisting collection of autonomous nodes that communicate with each other in decentralized manner. Security remains major challenge due to its some unique characteristics like open medium, mobility and hence topology changes. Therefore, routing protocol for MANETs is much vulnerable to attacks. Black Hole is a type of attack, where malicious node falsely advertises itself having the shortest or optimal path to the destination node. This attack is more dangerous while a group of nodes are cooperating with each other.The objective of this paper is to design cluster based routing protocol and prevent it from the black hole attack. The simulation results show improvement in packet delivery ratio and control overhead.